2007
DOI: 10.1109/tasc.2007.899703
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Nb$_{3}$Sn RRP Strands and Cables Based on a 108/127 Stack Design

Abstract: Abstract-The high performance Nb 3 Sn strand produced by Oxford Superconducting Technology (OST) with the Restack Rod Process (RRP) is presently considered as a baseline conductor for the Fermilab's accelerator magnet R&D program. To improve the strand stability in the current and field range expected in magnet models, the number of subelements in the strand was increased by a factor of two (from 54 to 108), which resulted in a smaller effective filament size. The performance of the 1.0 and 0.7 mm strands of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…The MJR strand had higher critical current density J c (12T, 4.2K)~2-2.2 kA/mm 2 and larger filament size d eff~1 00-110 μm whereas PIT strand had lower J c~1 .6-1.8 kA/mm 2 and smaller d eff~5 0-60 μm [2]. A new improved strand based on Restack Rod Process (RRP) was recently developed by Oxford Superconductor Technologies [3]. This strand provides highest Jc (<3 kA/mm 2 ) and has a larger number of sub-elements with smaller size (~70 μm).…”
Section: Q the Quementioning
confidence: 99%
See 3 more Smart Citations
“…The MJR strand had higher critical current density J c (12T, 4.2K)~2-2.2 kA/mm 2 and larger filament size d eff~1 00-110 μm whereas PIT strand had lower J c~1 .6-1.8 kA/mm 2 and smaller d eff~5 0-60 μm [2]. A new improved strand based on Restack Rod Process (RRP) was recently developed by Oxford Superconductor Technologies [3]. This strand provides highest Jc (<3 kA/mm 2 ) and has a larger number of sub-elements with smaller size (~70 μm).…”
Section: Q the Quementioning
confidence: 99%
“…The scale-up is performed in two steps starting with a 2-m long coil made of PIT Nb 3 Sn strand which has demonstrated the good stability and reproducible performance. This will be followed by 4-m long coil dipole mirror models were fabricated and tested at Fermilab.…”
Section: Technology Scale Upmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of these studies are reported elsewhere [10]. The third mirror model TQM03 was assembled with a new TQ coil made of improved Nb 3 Sn RRP strand of 108/127 design [11] with more spaced subelements [12]. The cable for this coil was fabricated using Fermilab's cabling machine [13] and insulated with E-glass tape using standard cable insulating technique.…”
Section: Tqm Mirror Model Assembly and Instrumentationmentioning
confidence: 99%